Alice's adventures in Wonderland - Carroll, Lewis, 1832-1898.; Tenniel, John, Sir, 1820-1914 (New York : Puffin, 2008)
Alice falls down a rabbit hole and discovers a world of nonsensical and amusing characters.
Keywords: Fantasy